Pengaruh Sektor Pariwisata terhadap Pendapatan Asli Daerah Provinsi Sumatera Barat - Leli Sumarni; Muhammad Fiqih Alfarudzi; Nini Syofri Yeni (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to analyze the influence of the tourism sector on Original Local Revenue of West Sumatra Province. This study will analyze how the influence of independent variables (number of tourist attractions, number of domestic tourists, number of restaurants and restaurants, and number of hotels and inns) on the dependent variable (Original Local Revenue) in West Sumatra Province. This study uses a quantitative method in the form of multiple regression analysis with panel data. The data used in this study is panel data for 5 years, namely from 2016 to 2020 obtained from the Central Statistics Agency (BPS) of West Sumatra Province. The results of the analysis using a fixed effect model approach show that the variable number of tourist objects had no effect nor was it significant on Original Local Revenue, the number of domestic tourists had a positive but not significant effect on Original Local Revenue, the number of hotels and inns, the number of restaurants and restaurants had a significant effect on increasing Original Local Revenue of West Sumatra Province.